Terrorism from within: an economic model of terrorism - S. Brock Blomberg; Gregory D. Hess; Akila Weerapana (Claremont McKenna College, Department of Economics, 2002)
In this paper, we develop and explore the implications of an economic model that links the incidence of terrorism in a country to the economic circumstances facing that country. We briefly sketch out a theory, in the spirit of Tornell (1998), that describes terrorist activities as being initiated by groups that are unhappy with the current economic status quo, yet unable to bring about drastic political and institutional changes that can improve their situation. Such groups with limited access to opportunity may find it rational to engage in terrorist activities. The result is then a pattern of reduced economic activity and increased terrorism. In contrast, an alternative environment can emerge where access to economic resources is more abundant and terrorism is reduced. Our empirical results are consistent with the theory. We find that for democratic, high income countries, economic contractions (i.e. recessions) can provide the spark for increased probabilities of terrorist activities.
Keywords: 330; Politische Gewalt; Wirtschaftskrise; Politische Unruhen; Public Choice; Institutioneller Wandel; Schätzung; Theorie; Welt